2009
DOI: 10.1017/s1368980008004072
|View full text |Cite
|
Sign up to set email alerts
|

Iron intake does not significantly correlate with iron deficiency among young Japanese women: a cross-sectional study

Abstract: Objectives: We evaluated the association of nutrient intake with Fe deficiency with regard to lifestyle factors and health condition in young Japanese women. Uniquely among developed countries, dietary habits render Japanese populations vulnerable to Fe deficiency, owing to their relatively low intake of Fe and high intake of Fe absorption inhibitors, such as green tea and soyabeans. Design: A cross-sectional study. Setting and subjects: The subjects were 1019 female Japanese dietetic students aged 18-25 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 72 publications
2
39
0
1
Order By: Relevance
“…[76] found dietary calcium intake to be inversely associated with serum ferritin concentration, regardless of whether calcium was consumed with iron. Other studies, however, have found no association between iron status and calcium [47,48,49,50,54,56,57] or dairy product or milk intake [45,49,50,59,66]. It has been suggested that in some cases, the negative associations between iron status and calcium or dairy product intake may be due to the displacement of other foods from the diet (e.g., meat), rather than the inhibitory effect of calcium itself [48].…”
Section: Dietary Determinants Of Iron Status In Young Women Livingmentioning
confidence: 94%
See 4 more Smart Citations
“…[76] found dietary calcium intake to be inversely associated with serum ferritin concentration, regardless of whether calcium was consumed with iron. Other studies, however, have found no association between iron status and calcium [47,48,49,50,54,56,57] or dairy product or milk intake [45,49,50,59,66]. It has been suggested that in some cases, the negative associations between iron status and calcium or dairy product intake may be due to the displacement of other foods from the diet (e.g., meat), rather than the inhibitory effect of calcium itself [48].…”
Section: Dietary Determinants Of Iron Status In Young Women Livingmentioning
confidence: 94%
“…The majority of cross-sectional studies in young women have not found an association between total dietary iron intake and iron status [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59]. Those studies showing a positive relationship included women aged 35 to 60 years [60], and a study which showed a positive relationship between iron intake and serum ferritin concentrations in smokers only [61].…”
Section: Dietary Determinants Of Iron Status In Young Women Livingmentioning
confidence: 99%
See 3 more Smart Citations